Pengaruh Perencanaan Pajak, Prudence, dan Biaya Agensi Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di BEI Periode 2016-2020) - Vivi Yani; Hari Stiawan (Yayasan Literasi Sains Indonesia, 2022)
This study aims to analyze the effect of tax planning, prudence, and agency costs on firm value. The independent variables in this study are tax planning which is measured using the effective tax rate, prudence is measured by using accrual conservatism, and agency costs are measured using free cash flow. The dependent variable in this study is firm value which is measured using price book value. This study uses descriptive analysis with a quantitative approach that uses secondary data. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique used is purposive sampling so that the selected sample is 11 companies selected based on the sample criteria, so that a total sample of 55 companies is obtained from the total sample of 11 times the research period for 5 years. The analysis technique in this study uses statistical data regression analysis of multiple linear regression analysis. The results of this study indicate that tax planning has a negative effect on firm value, prudence does not have a significant effect on firm value, and agency costs have a significant effect on firm value.